Phylogenetic evidence that both ancient vicariance and dispersal have contributed to the biogeographic patterns of anchialine cave shrimps - José A. Jurado-Rivera (Nature Portfolio, 2017)
Abstract Cave shrimps from the genera Typhlatya, Stygiocaris and Typhlopatsa (Atyidae) are restricted to specialised coastal subterranean habitats or nearby freshwaters and have a highly disconnected distribution (Eastern Pacific, Caribbean, Atlantic, Mediterranean, Madagascar, Australia). The combination of a wide distribution and a limited dispersal potential suggests a large-scale process has generated this geographic pattern. Tectonic plates that fragment ancestral ranges (vicariance) has often been assumed to cause this process, with the biota as passive passengers on continental blocks. The ancestors of these cave shrimps are believed to have inhabited the ancient Tethys Sea, with three particular geological events hypothesised to have led to their isolation and divergence; (1) the opening of the Atlantic Ocean, (2) the breakup of Gondwana, and (3) the closure of the Tethys Seaway. We test the relative contribution of vicariance and dispersal in the evolutionary history of this group using mitochondrial genomes to reconstruct phylogenetic and biogeographic scenarios with fossil-based calibrations. Given that the Australia/Madagascar shrimp divergence postdates the Gondwanan breakup, our results suggest both vicariance (the Atlantic opening) and dispersal. The Tethys closure appears not to have been influential, however we hypothesise that changing marine currents had an important early influence on their biogeography.